Haploid genetic screens identify an essential role for PLP2 in the downregulation of novel plasma membrane targets by viral E3 ubiquitin ligases. - Richard T Timms; Lidia M Duncan; Iva A Tchasovnikarova; Robin Antrobus; Duncan L Smith; Gordon Dougan; Michael P Weekes; Paul J Lehner (PLoS Pathogens, 2013)
The Kaposi's sarcoma-associated herpesvirus gene products K3 and K5 are viral ubiquitin E3 ligases which downregulate MHC-I and additional cell surface immunoreceptors. To identify novel cellular genes required for K5 function we performed a forward genetic screen in near-haploid human KBM7 cells. The screen identified proteolipid protein 2 (PLP2), a MARVEL domain protein of unknown function, as essential for K5 activity. Genetic loss of PLP2 traps the viral ligase in the endoplasmic reticulum, where it is unable to ubiquitinate and degrade its substrates. Subsequent analysis of the plasma membrane proteome of K5-expressing KBM7 cells in the presence and absence of PLP2 revealed a wide range of novel K5 targets, all of which required PLP2 for their K5-mediated downregulation. This work ascribes a critical function to PLP2 for viral ligase activity and underlines the power of non-lethal haploid genetic screens in human cells to identify the genes involved in pathogen manipulation of the host immune system.